How do you solve #x(x+6)=-2# using the quadratic formula?

1 Answer
Oct 31, 2017

Answer:

When given an equation of the form, #ax^2+bx+c = 0#, one can find the value(s) of x by substituting the values for a, b, and c into the quadratic formula:

#x = (-b+-sqrt(b^2-4(a)(c)))/(2a)#

Explanation:

The given equation #x(x+6)=-2# is not in the form specified in the answer, therefore, we must put it in that form.

Use the distributive property on the left side:

#x^2 + 6x = -2#

Add 2 to both sides:

#x^2 + 6x +2= 0#

By observation, #a = 1, b = 6, and c = 2#

Substitute these values into the quadratic formula:

#x = (-6+-sqrt(6^2-4(1)(2)))/(2(1))#

#x = (-6+-sqrt(36-8))/2#

#x = (-6+-sqrt(28))/2#

#x = (-6+-2sqrt7)/2#

#x = -3+-sqrt7#

#x = -3-sqrt7# and #x = -3+sqrt7#